ISOLASI DAN KARAKTERISASI BAKTERI ASAM LAKTAT DARI LIMBAH CAIR RENDAMAN KACANG KEDELAI - Zakiyah Zahra Nur Amaliah; Saiful Bahri; Puteri Amelia (Jurnal Fitofarmaka Indonesia, 2018)
Tempe is an Indonesia traditional food, which in the manufacturers have a liquid waste that no use again namely soybean soaking water. Lactic Acid Bacteria (LAB) has been known at every stage of tempeh production, included at soaking soybeans. This study aimed to isolate and characterize LAB contained in soybean soaking water liquid waste. After serial dilution to 10-7, soybean soaking water liquid waste was inoculated on the MRSA contained 1% CaCO3. After incubation, there are 8 isolates which produce clear zone around their colonies with different colony morphology suspected as LAB. Morphological, physiological and biochemical characteristics were employed to identify LAB. All isolates were non-spore forming, non-motile, catalase negative, grow well at 37° and 45°C, could be able to grow in the presence of 4% and 6.5% sodium chloride. The results of safety test showed all isolates negative for hemolytic activity. Seven of eight isolates are Gram-positive, while one is a Gram-negative. But only Gram-positive were chosen as they represent the LAB characteristic. Seven isolates were identified as Lactobacillus with heterofermentative as the type fermentation. In this study, Lactobacillus casei ATCC 393 used as reference strain